Implementasi Pembelajaran IPA Berbasis Literasi Sains untuk Meningkatkan Pemahaman Konsep Sistem Biologis Siswa Kelas IX MTs - Yayat Rohayati (CV. Intake Pustaka, 2025)
Science learning at the Islamic Junior High School (Madrasah Tsanawiyah) level requires meaningful connections between scientific concepts and real-life phenomena familiar to students. One relevant contextual learning resource is the use of local food materials, such as guava (Psidium guajava), which is rich in vitamin C. This study aims to analyze the effect of science learning based on scientific literacy through the study of vitamin C content in guava on students’ understanding of biological system concepts, particularly the role of nutrients in collagen formation, among ninth-grade students of MTs YPK Cijulang, Pangandaran Regency. The research employed a quasi-experimental method with a one-group pretest–posttest design. The research subjects were ninth-grade students who participated in science learning using contextual teaching materials based on local food resources. Research instruments included a conceptual understanding test and student activity observation sheets. The results showed an improvement in students’ conceptual understanding after the implementation of contextual learning, as indicated by higher posttest scores compared to pretest scores. Science learning that integrates nutrition concepts, vitamins, and human biological systems using guava as a study object effectively enhanced student engagement and scientific literacy. Therefore, the use of local context in science learning has the potential to improve learning quality and conceptual understanding of ninth-grade MTs students.